Pediatric Acute-Onset Neuropsychiatric Syndrome: Current Perspectives - Gagliano A; Carta A; Tanca MG; Sotgiu S (Neuropsychiatric Disease and Treatment, 2023)
Antonella Gagliano,1,2 Alessandra Carta,3 Marcello G Tanca,2 Stefano Sotgiu3 1Department of Health Science, “Magna Graecia” University of Catanzaro, Catanzaro, Italy; 2Department of Biomedical Sciences, University of Cagliari & “A. Cao” Paediatric Hospital, Child & Adolescent Neuropsychiatry Unit, Cagliari, Italy; 3Department of Medicine, Surgery and Pharmacy, University of Sassari, Unit of Child Neuropsychiatry, Sassari, ItalyCorrespondence: Alessandra Carta, Department of Medicine Surgery and Pharmacy University of Sassari, Complex Operating Unit of Child Neuropsychiatry, Sassari, Sardinia, 07100, Italy, Tel +39 3405438579, Fax +39 079 229325, Email alessandra.carta@aouss.itAbstract: Pediatric acute-onset neuropsychiatric syndrome (PANS) features a heterogeneous constellation of acute obsessive-compulsive disorder (OCD), eating restriction, cognitive, behavioral and/or affective symptoms, often followed by a chronic course with cognitive deterioration. An immune-mediated etiology is advocated in which the CNS is hit by different pathogen-driven (auto)immune responses. This narrative review focused on recent clinical (ie, diagnostic criteria, pre-existing neurodevelopmental disorders, neuroimaging) and pathophysiological (ie, CSF, serum, genetic and autoimmune findings) aspects of PANS. We also summarized recent points to facilitate practitioners with the disease management. Relevant literature was obtained from PubMed database which included only English-written, full-text clinical studies, case reports, and reviews. Among a total of 1005 articles, 205 were pertinent to study inclusion. Expert opinions are converging on PANS as the effect of post-infectious events or stressors leading to “brain inflammation”, as it is well-established for anti-neuronal psychosis. Interestingly, differentiating PANS from either autoimmune encephalitides and Sydenham’s chorea or from alleged “pure” psychiatric disorders (OCD, tics, Tourette’s syndrome), reveals several overlaps and more analogies than differences. Our review highlights the need for a comprehensive algorithm to help both patients during their acute distressing phase and physicians during their treatment decision. A full agreement on the hierarchy of each therapeutical intervention is missing owing to the limited number of randomized controlled trials. The current approach to PANS treatment emphasizes immunomodulation/anti-inflammatory treatments in association with both psychotropic and cognitive-behavioral therapies, while antibiotics are suggested when an active bacterial infection is established. A dimensional view, taking into account the multifactorial origin of psychiatric disorders, should suggest neuro-inflammation as a possible shared substrate of different psychiatric phenotypes. Hence, PANS and PANS-related disorders should be considered as a conceptual framework describing the etiological and phenotypical complexity of many psychiatric disorders.Keywords: PANS, obsessive-compulsive disorder, neuroinflammation, CNS autoimmunity, PANS management